Love Without End : a Kings Meadow Romance - Hatcher, Robin Lee. (Nashville : Thomas Nelson, 2014)
"For two single parents with bruised hearts, it'll take more than a little courage to get back on the horse when it comes to love"--Page 4 of cover.
Keywords: Single parents -- Fiction; Man-woman relationships -- Fiction; Life change events -- Fiction; Family crises -- Fiction; Horses -- Fiction; Christian fiction; Love stories